The Effect of Return on Investment (ROI), Debt to Equity Ratio (DER) and Sales Growth on Firm Value (Case Study of Manufacturing Companies in the Industrial Sector for the 2020–2024 Period) - Halimah Tusoleha; Nurul Kamila (PT Ilmu Data Indonesia, 2026)
This study aims to analyze the effect of Return on Investment (ROI), Debt to Equity Ratio (DER), and Sales Growth on Firm Value in manufacturing companies in the industrial sector listed on the Indonesia Stock Exchange during the 2020–2024 period. Firm value is measured using Price to Book Value (PBV). This research is motivated by the fluctuating condition of Indonesia’s manufacturing sector caused by global and domestic economic uncertainty, which has affected profitability and investor confidence in companies. This research uses a quantitative method with an explanatory approach. The data used are secondary data obtained from companies’ annual financial reports. The sampling technique applied is purposive sampling, resulting in 28 companies as research samples with a total of 140 observation data. Data analysis was conducted using SPSS through descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The results show that partially, Return on Investment (ROI) has a negative and significant effect on Firm Value, Debt to Equity Ratio (DER) has a positive and significant effect on Firm Value, while Sales Growth has a negative and significant effect on Firm Value. Simultaneously, ROI, DER, and Sales Growth significantly affect Firm Value. The findings of this study are expected to provide consideration for companies and investors in making decisions related to financial management and investment activities.